KEGIATAN PEMBELAJARAN DALAM PENDEKATAN PENGAJARAN BAHASA KOMUNIKATIF DI LPIA (LEMBAGA PENDIDIKAN INDONESIA AMERIKA) DI TERNATE - HABU, YULIANA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT This research entitled â€LearningÂ  Activities in Communicative Language Teaching in LPIA (Lembaga Pendidikan Indonesia Amerika)Â  Ternateâ€ is an attempt to identify and analyze the activities used inÂ  communicative language teaching especially in LPIA Ternate. The concept of Moss (2005) on CLT activities is used to identify the learning activities used in LPIA. These activities are conversation grids, questionnaires, games, information gap, problem solving activities, discussion, and role-play. The data of this research were taken by interviewing the teachers in LPIA and by observing five classes with 25 studentsâ€™ in each class, about one hour. The data show that the activities of communicative language teaching that were used in LPIA Ternate, are games, pair work or group work and discussion. There are two other additional activities used in class. They areÂ  debate class and e-trip. The results of this research show that the learning activities used inÂ  LPIA Ternate support Mossâ€™ concept. These CLT activities are games, pair work or group work and discussion. Additionally, there are two other CLT activities that were found or used in LPIA. TheyÂ  areÂ  debate class and e-trip. Â  Keywords : CLT activities, debate class, games, E-trip, discussion